BENTUK DAN IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY TERHADAP KESEJAHTERAAN EKONOMI PETANI SEKITAR TAMBANG PT.ANTAM DI DESA HUKO-HUKO KECAMATAN POMALAA - Rahma Muhlis; Iskandar Zainuddin Rela; Anas Nikoyan (Universitas Halu Oleo, 2022)
This research is motivated by the form of the CSR program conducted at PT. Antam in improving the economic welfare of farmers around the PT. Antam in Huko-Huko Village. As well as seeing the implementation of CSR programs in improving the economic welfare of farmers around the PT. Antam mine in Huko-Huko Village. This study uses a qualitative method with 25 informants based on purposive sampling technique. The data analysis used is (1) data reduction, (2) data presentation, (3) preliminary conclusions and using special analysis. The results of this study indicate that (1) The form of the CSR program in Huko-Huko Village includes the Community Development program which consists of education and development of facilities/infrastructure that supports the welfare of farmers. This program has a positive impact on the farming community because the CSR program provides solutions to solve problems faced by farming families related to assistance in education programs and the development of farmer facilities/infrastructure. (2). Implementation of the CSR program which includes the planning stage, implementation stage, monitoring stage, and reporting stage. Which is carried out by CSR PT. Antam and other institutions. Although these stages have not fully realized the economic welfare of farmers, compared to the previous one, there has been an increase in the living standards of the farming community, thus the CSR program that has been implemented has contributed a lot to the farming community in Huko-Huko Village, Pomalaa District, Kolaka Regency